Menggagas Bentuk Ruang Kota Alternatif: Upaya Mereduksi Intensitas Pegerakan Lalu Lintas Kota - Iwan P. Kusumantoro (The Institute for Research and Community Services, Institut Teknologi Bandung, 2007)
This paper aims to provide answerto the classical questions of the impact of spatial design or urban form to induce trip pattern. How policy makers should be advised with regard to the use of urban spatial structure design and land use tools to reduce traffic in urban area? Although some relationships between land use and travel appear straight forward, such as density and trip lenght these simple observed correlations are not so simple upon closer examination. Land use and travel linkages are both multidimensional and difficult to deconstruct. Rather, they represent complex interactions of many factors. How should researchers proceed? Any empirical work of this nature is problematic given the enormous complexity of the activities to be explained and difficulties in conceptualizing the interaction between travel and spatial structure. The usefulness of land use and transportation approaches, including alternatives approach such as new urbanism and smart growth, is frequently assessed based on the capacity of these innovations to reduce auto use. Compaction is a typical structure of an alternatives approach of urban form. The preliminary finding of the research in the surrounding areas of Bandung, Semarang, and Cilegon, shows a different conclusion with the theoritical description of